The protective effect of food matrices on Listeria lytic bacteriophage P100 application towards high pressure processing. (December 2018) - Komora, Norton; Bruschi, Carolina; Ferreira, Vânia; Maciel, Cláudia; Brandão, Teresa R.S.; Fernandes, Rui; Saraiva, Jorge A.; Castro, Sónia Marília; Teixeira, Paula
Abstract: The application of lytic phages as biocontrol agents is emerging as a promising strategy towards elimination or reduction of foodborne pathogens in a variety of food products. This technology is particularly advantageous for minimally processed and ready-to-eat (RTE) foods. In this study, the potential use of Listex™ P100 combined with high hydrostatic pressure (HPP), to enhance the control of Listeria monocytogenes in food was evaluated. For that, the effect of three pressures (200, 300 or 400 MPa; 5 min, 10 °C) on phage P100 stability was tested when inoculated in six different matrices: phosphate buffered saline (PBS, pH 7.4); apple juice (pH 3.41); orange/carrot nectar (pH 3.54); UHT whole milk (pH 6.73); and, two traditional Portuguese fermented products, "Serra da Estrela" cheese (pH 5.66) and "Alheira", a meat sausage (pH 6.07). The results showed that treatment at 400 MPa reduced phage titres to below the detection level in all matrices, whereas at milder pressures the survival of the phage was matrix dependent. "Alheira", "Serra da Estrela" cheese and UHT whole milk were shown to be baroprotective matrices that support phage P100 application in HHP up to 300 MPa; however, an accentuated phage inactivation was observed in apple and orange/carrot nectar, which may be related to the acidic pH values of these matrices. The initial phage load did not affect the inactivation rate during HHP processing (300 MPa, 5 min, 10 °C) in PBS, cheese, sausage or milk matrices, and the phage titres were stable in these matrices during storage at 4 °C for 28 days for milk and 60 days for "Alheira" and "Serra da Estrela" cheese. In addition, a baroprotective effect on phage stability was observed when PBS was supplemented with reducing sugars, dextrin, casein, and tween 80. In conclusion, at mild HHP treatment, phage P100 remained active in specific matrices and seems to present potential to be added in non-thermal inactivation of L. monocytogenes . Highlights: Antilisterial activity of Listex™ combined with high hydrostatic pressure investigated. Effect of 200, 300 or 400 MPa on phage stability tested in six matrices. 400 MPa reduced phage titres to below the detection level in all matrices. "Alheira", "Serra da Estrela" cheese and UHT whole milk were baroprotective matrices. Reducing sugars, dextrin, casein, and tween 80 demonstrated a baroprotective effect.